2017
DOI: 10.1371/journal.pone.0187834
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine effectiveness against laboratory-confirmed influenza hospitalizations among young children during the 2010-11 to 2013-14 influenza seasons in Ontario, Canada

Abstract: Uncertainty remains regarding the magnitude of effectiveness of influenza vaccines for preventing serious outcomes, especially among young children. We estimated vaccine effectiveness (VE) against laboratory-confirmed influenza hospitalizations among children aged 6–59 months. We used the test-negative design in hospitalized children in Ontario, Canada during the 2010–11 to 2013–14 influenza seasons. We used logistic regression models adjusted for age, season, and time within season to calculate VE estimates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…This study was limited by the unavailability of data regarding influenza vaccination in prior seasons. Although studies examining the effect of prior influenza vaccination on current season VE have shown variable results [34][35][36][37][38][39][40][41], most evidence to date suggests that influenza A (H3N2) VE estimates are highest when vaccination is administered during the season that is being evaluated [20,38].…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited by the unavailability of data regarding influenza vaccination in prior seasons. Although studies examining the effect of prior influenza vaccination on current season VE have shown variable results [34][35][36][37][38][39][40][41], most evidence to date suggests that influenza A (H3N2) VE estimates are highest when vaccination is administered during the season that is being evaluated [20,38].…”
Section: Discussionmentioning
confidence: 99%
“…The CCC is preferentially used to identify comorbidities in children. We used the same codes as previous studies identifying CCC from the ICES administrative databases [15].…”
Section: Patientsmentioning
confidence: 99%
“…RV-positive children were second youngest after RSV-positive children while IFAV-positive children were generally older than those positive for any other virus. Interestingly, it is often children younger than 2 years who are affected by severe influenza [ 46 ]. Most RV detections (single or multiple) occurred in infants, the largest contributing population.…”
Section: Discussionmentioning
confidence: 99%